Hybrid reliability analysis with uncertainty in correlation coefficients and first two statistical moments (REC 2026 - 11th International Workshop on Reliable Engineering Computing: Reliability Computations in a Data and Model-Driven World, 2026)
Traditional reliability analysis aims to evaluate the failure probability of structures under the presence of aleatory uncertainties. However, in real-world applications, limited data often introduces epistemic uncertainties, requiring the use of hybrid reliability analysis. In this study, to address the epistemic uncertainty caused by insufficient data, both the statistical moments and the correlation coefficients of the random variables are uncertain, and are represented using interval variables. With the aid of the simplified third-moment normal transformation model, the values of uncertain moments and correlation coefficients of each random variables that lead to the bounds of failure probability are determined. The bounds of the failure probability are then evaluated through two traditional reliability analyses. The proposed method is demonstrated through two examples.